Effect of communicating DNA based risk assessments for Crohn's disease on smoking cessation: randomised controlled trial. (20th July 2012) - Hollands, Gareth J; Whitwell, Sophia C L; Parker, Richard A; Prescott, Natalie J; Forbes, Alastair; Sanderson, Jeremy; Mathew, Christopher G; Lewis, Cathryn M; Watts, Sally; Sutton, Stephen; Armstrong, David; Kinmonth, Ann Louise; et al.
Abstract : Objective To test the hypothesis that communicating risk of developing Crohn's disease based on genotype and that stopping smoking can reduce this risk, motivates behaviour change among smokers at familial risk. Design Parallel group, cluster randomised controlled trial. Setting Families with Crohn's disease in the United Kingdom. Participants 497 smokers (mean age 42.6 (SD 14.4) years) who were first degree relatives of probands with Crohn's disease, with outcomes assessed on 209/251 (based on DNA analysis) and 217/246 (standard risk assessment). Intervention Communication of risk assessment for Crohn's disease by postal booklet based on family history of the disease and smoking status alone, or with additional DNA analysis for the NOD2 genotype. Participants were then telephoned by a National Health Service Stop Smoking counsellor to review the booklet and deliver brief standard smoking cessation intervention. Calls were tape recorded and a random subsample selected to assess fidelity to the clinical protocol. Main outcome measure The primary outcome was smoking cessation for 24 hours or longer, assessed at six months. Results The proportion of participants stopping smoking for 24 hours or longer did not differ between arms: 35% (73/209) in the DNA arm versus 36% (78/217) in the non-DNA arm (difference −1%, 95% confidence interval −10% to 8%, P = 0.83). The proportion making a quit attempt within the DNA arm did not differ between those who were told they had mutations putting them at increased risk (36%), those told they had none (35%), and those in the non-DNA arm (36%). Conclusion Among relatives of patients with Crohn's disease, feedback of DNA based risk assessments does not motivate behaviour change to reduce risk any more or less than standard risk assessment. These findings accord with those across a range of populations and behaviours. They do not support the promulgation of commercial DNA based tests nor the search for gene variants that confer increased risk of common complex diseases on the basis that they effectively motivate health related behaviour change. Trial registration Current Controlled Trials ISRCTN21633644 .